Suwanee Lumber Company - Elias, Jaan; Blumenthal, Adam; Shovlin, James; Tookes, Heather E. (London : Yale School of Management, 2020)
In 2016, Blue Wolf, a private equity firm headquartered in New York City, confronted a number of options when it came to its lumber business. They could put their holdings in the Suwanee Lumber Company (SLC), a sawmill they had purchased in 2013, up for sale. Or they could continue to hold onto SLC and run it as a standalone business. Or they could double down on the lumber business by buying an idle mill in Arkansas to run along with SLC.
Originally Published InElias, J., Blumenthal, A., Shovlin, J., & Tookes, H.E. (2020). Suwanee Lumber Company. 20-010. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Investments -- Case studies; Business -- Case studies; Venture capital -- Case studies